Structural features of cross-language transformations within the translation of literary text (Park Wan Suh “Who Ate Up All the Shinga?”) (Вестник КазНУ. Серия Востоковедения, 2018)
The article considers the problem of national specifics in literary translation, which is regarded as anintegral part of the modern literary process, promotes the mutual enrichment and interrelation betweenthe world nations’ literatures and the development of international cooperation in science, culture andeducation. It is known that literary translation is a special kind of translation activity linked, on the onehand, to the secondary reproducing nature of translation, on the other hand - in the process of translationto the need to create texts with the ability of direct aesthetic impact. Translator have to maintain amediating authenticity, proximity to the original text, and at the same time to be able to create a workof art in target language and culture which will be equivalent to original. That is two divergent kinds ofspeech activities, the perception of the original text and the creation of translated text are interact andoppose during the translation process.The problem of transmission of cultural identity and the preservation of the original text unique flavorin foreign language was always an acute problem for translators. The issues related to the re-creationof the so-called “unfamiliar reality” in the target language are most complex and at the same time relativelylittle developed. The article analyzes the translation of hieroglyphic phraseological units (HPU),culture of lexemes-realities and toponyms of Park Wan Suh novel “Forgotten acid taste”.